Diffusion tensor imaging and disability progression in multiple sclerosis: A 4‐year follow‐up study. Issue 1 (26th December 2018) - Kolasa, Marcin; Hakulinen, Ullamari; Brander, Antti; Hagman, Sanna; Dastidar, Prasun; Elovaara, Irina; Sumelahti, Marja‐Liisa
Abstract: Objectives: Diffusion tensor imaging (DTI) is sensitive technique to detect widespread changes in water diffusivity in the normal‐appearing white matter (NAWM) that appears unaffected in conventional magnetic resonance imaging. We aimed to investigate the prognostic value and stability of DTI indices in the NAWM of the brain in an assessment of disability progression in patients with a relapsing‐onset multiple sclerosis (MS). Methods: Forty‐six MS patients were studied for DTI indices (fractional anisotropy (FA), mean diffusivity (MD), radial (RD), and axial (AD) diffusivity) in the NAWM of the corpus callosum (CC) and the internal capsule at baseline and at 1 year after. DTI analysis for 10 healthy controls was also performed at baseline. Simultaneously, focal brain lesion volume and atrophy measurements were done at baseline for MS patients. Associations between DTI indices, volumetric measurements, and disability progression over 4 years were studied by multivariate logistic regression analysis. Results: At baseline, most DTI metrics differed significantly between MS patients and healthy controls. There was tendency for associations between baseline DTI indices in the CC and disability progression ( p  < 0.05). Changes in DTI indices over 1 year were observed only in the CC ( p  < 0.008), and those changes were not found to predict clinical worsening over 4 years. Clear‐cut association with disability progression was not detected for baseline volumetric measurements. Conclusion: Aberrant diffusivity measures in the NAWM of the CC may provide additional information for individual disability progression over 4 years in MS with the relapsing‐onset disease. CC may be a good target for DTI measurements in monitoring disease activity in MS, and more studies are needed to assess the related prognostic potential. Abstract : Baseline DTI indices in the CC splenium were associated with 4‐year disability progression in MS. One‐year DTI changes were not linked to 4‐year disability progression. Dynamic change in DTI over time is different with respect to anatomical location. Disease progression showed heterogeneity and temporal DTI changes in the brain regions seem to occur with individual rate. DTI is sensitive to diffusivity abnormalities in the specific brain regions responsible for disability accumulation and to longitudinal changes in diffusivity.